How the other half lives : studies among the tenements of New York. - Riis, Jacob A. (Jacob August), 1849-1914; Museum of the City of New York. (New York : Dover, 1971)
This famous journalistic record of the filth and degradation of New York's slums at the turn of the century is a classic in social thought and a monument of early American photography. Captured on film by photographer, journalist, and reformer Jacob Riis, more than 100 grim scenes reveal man's struggle to survive.
"An unabridged republication of the text of the 1901 edition ... A new preface has been written specially for the present edition."
Keywords: Poor -- New York (State) -- New York; Tenement houses -- New York (State) -- New York